KEMIRIPAN DAN KEUNGGULAN KREDIT MODAL KERJA (KMK) BANK PEMBANGUNAN DAERAH BALI DENGAN BEBERAPA BANK PESAING - I Made Purba Astakoni (Forum Manajemen STIMI Handayani Denpasar, 2015)
The aim of this study were 1) to determine the similarity (similarity)between product Working Capital Loan (KMK) BPD Bali with competing products.2) to determine the debtor’s perception of the product Working Capital Loans (WCL)BPD Bali and the products of its competitors. 3) to determine the superiority ofWorking Capital Loans (WCL) BPD Bali compared with competing products. The dataanalysis technique used is a multivariate analysis, the analysis of multidimensionalscaling (MDS) and Correspondence Analysis (CA). Based on the analysis of MDS in particular two-dimensional perceptual map, customer perception of similarity between the bank shows that the KMK BPD Bali has similarities with KMK BRI, whileKMK BNI has some similarities with Bank Mandiri. From the analysis of respondents’perceptions CA KMK BPD Bali showed the same position with the KMK BRI with anaverage score of 82.92 percent,. KMK BNI 46 with an average score of 84.42 percent,KMK bank Mandiri of 84.33 percent while the WCL Danamon lowest perceived witha score of 81.83 percent. KMK BRI BPD Bali and excels in ease of loan collateralattributes, and attribute lending. While KMK BNI and Bank Mandiri has advantagesin the cost of provision and administration attributes, office location / room acomfortable, personal approach and standard system attributes. While KMK BankDanamon has the advantage on account activity and attributes atributl advertising.